Testing spatial and environmental factors to explain body shape variation in the widespread Central American Blackbelt cichlid Vieja maculicauda (Teleostei: Cichlidae) - Diego A. Ardón; Caleb D. McMahan; Ernesto Velázquez-Velázquez; Wilfredo A. Matamoros (Neotropical Ichthyology, 2022)
Abstract Body-shape variability may respond to the interaction between history and environment, particularly in species whose range includes known biogeographical barriers. Central America has traditionally been regarded to have functioned as a complete land-bridge connecting two continents since the Plio-Pleistocene and as an incomplete one since much earlier. This history has helped shape species diversification and distributions. Vieja maculicauda is a widely distributed cichlid, found throughout most of the Atlantic slope of Central America, across three of the four geological blocks that make up this region and whose borders are known dispersal barriers. We asked whether there is an effect of geologic blocks on body shape of V. maculicauda as determined by geometric morphometric assessment of 151 individuals from across its range. We asked how much variance in body shape is explained by environmental variables. We used a CVA and a MANCOVA to determine whether a relationship between body shape and geologic blocks exists. For testing body shape correlation against geographic and environmental variables, we used a Mantel test. Our results suggest that body shape in V. maculicauda can be segregated by geologic blocks, while the correlation results showed no strong correlation between our sets of variables.